2018
DOI: 10.1002/aorn.12150
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta‐Analysis of Cricoid Pressure Training and Education Efficacy

Abstract: We examined the evidence on the effectiveness of education and training on cricoid pressure (ie, Sellick maneuver) application. Cricoid pressure is used during rapid sequence induction and intubation to reduce the risk of pulmonary aspiration. We searched seven databases for studies on the education and training of health care personnel expected to apply cricoid pressure as a part of their regular clinical responsibilities. We appraised the included studies using standardized tools validated for this purpose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 41 publications
(63 reference statements)
1
13
0
Order By: Relevance
“…6 Anesthesia professionals, hospital administrators, lawyers, and patients continue to accept cricoid pressure as a standard of care, especially for patients at high risk of regurgitation. 4,11,13 Therefore, health care providers should focus on improving their practice by developing curricula and creating skill-practice sessions to attain competency and improve patient outcomes. The controversy of employing or not employing cricoid pressure first requires that health care providers apply it correctly.…”
Section: Standard Of Carementioning
confidence: 99%
See 2 more Smart Citations
“…6 Anesthesia professionals, hospital administrators, lawyers, and patients continue to accept cricoid pressure as a standard of care, especially for patients at high risk of regurgitation. 4,11,13 Therefore, health care providers should focus on improving their practice by developing curricula and creating skill-practice sessions to attain competency and improve patient outcomes. The controversy of employing or not employing cricoid pressure first requires that health care providers apply it correctly.…”
Section: Standard Of Carementioning
confidence: 99%
“…8,12,75 Authors of another study found that 69% of anesthesia professionals "had never heard of any recommended level of force to be used for the application of cricoid pressure" 76(p1212) on an awake, semiconscious, or unconscious patient; again, other authors have found similar results. 5,13,34,61 A 20-year-old study focused on perioperative nurses found that 95% of participants could not state the recommended pressure to be applied. 12 Other studies have found that, in general, health care providers of all types often do not provide cricoid pressure correctly.…”
Section: Education and Training To Enhance Skill Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Simulated cricoid skill trainers, manikins, or digital scales can be effective tools for cricoid pressure training 6,9 . A systematic review evaluating the effectiveness of cricoid pressure training methods found consistent deficits in participants’ knowledge and abilities, and concluded that simulation methods were effective in improving knowledge of cricoid anatomy and the ability to apply the correct amount of pressure required.…”
Section: Assisting the Anesthesia Professionals With Cricoid Pressurementioning
confidence: 99%
“…A systematic review evaluating the effectiveness of cricoid pressure training methods found consistent deficits in participants’ knowledge and abilities, and concluded that simulation methods were effective in improving knowledge of cricoid anatomy and the ability to apply the correct amount of pressure required. Further, the authors acknowledged the valuable role that perioperative RNs play in preventing aspiration when assisting with intubation 9 …”
Section: Assisting the Anesthesia Professionals With Cricoid Pressurementioning
confidence: 99%